The Aesthetics of Embodied Vulnerabilities: Narrative Constructions of Entertainment in Infinite Jest. - Chapman, Ana María (Tirant lo Blanch, 2023)
This book explores David Foster Wallace's novel Infinite Jest (1996) from the perspective of vulnerability, disability studies and neuroscientific theories of subjectivity and agency. From this approach, this book offers insights regarding questions about body-mind connections and the interconnectivity/interdependence of others for subjectivity. In the search for happiness and entertainment, Wallace presents a world where characters? lives are in an annular quest for hedonistic pleasure. His encapsulated characters have no sense of control of actions or image, which gives way to abnormal body representation and mental disaffections, including emotional incapacity and group alienation/detachment. Light is also shed on how the representation of vulnerability, disability or "abnormalities," in terms of body and mind reveal the implication of individual entrapment in the entertainment world and thus, the lack of self-awareness, agency and subjectivity. Moreover, the analysis presents a contribution to the discussion of how Wallace?s reflection on contemporary society shows vulnerabilities as a narratological vehicle for understanding affective and interdependent relations to others for one?s own subjectivity and sense of agency.
Keywords: Wallace, David Foster - Crítica e interpretación; Posthumanism; Neuroscience; David Foster Wallace; Cognitive literature; vulnerability studies